The The relationship between pregnant women's nutritional status and the interpretation of fetal weight - Mufida Annisa Rahmawati; Fitria Aisyah; Woro Tri Utami (CV. LINK Education Publication, 2025)
Introduction: Inadequate nutritional intake during pregnancy can impact fetal weight, increasing the risk of low birth weight (LBW), i.e., less than 2500 grams. Low birth weight is a contributing factor to increased infant mortality rates (IMR), and the success of maternal health efforts can be measured by the maternal mortality rate (MMR). Fetal weight estimation is a crucial indicator for neonatal and infant survival, not only as a parameter of physical growth and mental development, but also as a general benchmark for assessing health, nutritional, and socioeconomic status. Objectives: This study aimed to find out the relationship between the nutritional status of pregnant women and the estimated fetal weight in Songgokerto. Methods: This research approach uses Cross Sectional. The population in this study was 30 pregnant women. The sample taken was 30 pregnant women. The instruments used were questionnaires, KIA books, nutritional status observation sheets. The sampling technique was total sampling. Data analysis using simple linear regression. Results: The calculated t value of the nutritional status variable of pregnant women is 39.205 > t table 2.045, meaning there is a significant relationship between the nutritional status of pregnant women and the estimated fetal weight. The calculated F value of 1537.026 > from the F value of 0.05 (4.20) means that there is a significant simultaneous relationship between the nutritional status of pregnant women and the estimated fetal weight. Conclusion: There is a significant relationship between the nutritional status of pregnant women and the interpretation of fetal weight.